2013
DOI: 10.1161/circresaha.112.273375
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Bioenergetics Is an Important Determinant of the Molecular Imaging Signal Derived From Luciferase and the Sodium-Iodide Symporter

Abstract: Rationale Molecular imaging is useful for longitudinal assessment of engraftment. However, it is not known which factors, other than cell number can influence the molecular imaging signal obtained from reporter genes. Objective The effects of cell dissociation/suspension on cellular bioenergetics and the signal obtained by firefly luciferase(fluc) and human Na-I symporter(hNIS) labeling of cardiosphere-derived cells (CDCs) was investigated. Methods and Results 18FDG uptake, ATP levels, 99mTc-pertechnetate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Chang and colleagues (162) transduced NIS into cardiosphere-derived cells (CDCs) to determine how different methods of cell separation prior to injection would affect cell metabolism and bioenergetics and ultimately the efficiency of the engraftment of the cells. Their results may eventually help optimize the preparation conditions for CDC transplantation.…”
Section: Nis As a Valuable Molecule To Monitor The Fate Of Stem Cellsmentioning
confidence: 99%
“…Chang and colleagues (162) transduced NIS into cardiosphere-derived cells (CDCs) to determine how different methods of cell separation prior to injection would affect cell metabolism and bioenergetics and ultimately the efficiency of the engraftment of the cells. Their results may eventually help optimize the preparation conditions for CDC transplantation.…”
Section: Nis As a Valuable Molecule To Monitor The Fate Of Stem Cellsmentioning
confidence: 99%
“…We have previously demonstrated that cell dissociation and suspension rapidly down regulate glucose uptake, metabolism and ATP levels[1]; suspension also predisposes cells to anoikis[25, 26]. Stem cells utilize glucose as their main energy source[27].…”
Section: Resultsmentioning
confidence: 99%
“…The cDNA encoding the hNIS (human sodium iodide symporter) gene or the cDNA pGL4.10[luc2] encoding firefly luciferase (Promega) was sub-cloned in place of eGFP into the vector RRLsin18.cPPT.CMV.eGFP.Wpre, resulting in plasmids designated cpPPT.CMV.hNIS or pPPT.CMV.fLuc as previously described[1]. Viral vectors were produced and titered as described previously[1]. For genetic labeling, rat CDCs were transduced at a multiplicity of infection (MOI) of 20, yielding transduction efficiencies of >70% for hNIS expression and >90% for fLuc expression.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations